AI in Higher Education: A Survey of Artificial Intelligence Usage in Students English Academic Writing (Conference on English Language Teaching, 2025)
This study investigates the integration and application of Artificial Intelligence (AI) in English-language academic writing within the Faculty of Ushuluddin and Dakwah at UIN Raden Mas Said Surakarta. As AI tools become increasingly prevalent in academic environments, their role in enhancing research quality, language proficiency, and academic writing has gained significance. Through a survey-based approach, this research examines how students utilize AI tools such as grammar checkers, translation engines, citation generators, and content assistants during the research and writing process to compile the academic writing. The findings reveal patterns of usage, perceived benefits, ethical concerns, and potential dependency on AI technologies. This paper also discusses the implications of AI usage for academic integrity, originality, and the development of independent scholarly skills. The study concludes by recommending guidelines for the responsible and effective use of AI in academic research within the Islamic and social sciences context especially to do academic writing task.